The role of national qualifications systems in promoting lifelong learning : towards an understanding of the mechanisms that link qualifications and lifelong learning - Behringer, Friederike [Verfasser]; Coles, Mike [Verfasser] (OECD Publishing, 2003)
"The aim of the OECD activity The Role of National Qualifications Systems in Promoting Lifelong Learning is to investigate how qualifications systems influence the volume, distribution and quality of lifelong learning. This paper takes forward thinking about the ways in which qualifications systems can influence participation in lifelong learning (LLL) and the quality of learning experiences. A set of 11 components and some 60 subcomponents of qualifications systems is proposed and delineated and LLL is described by a set of 18 indicators. If there are relationships between qualifications systems and lifelong learning that are not just spurious correlations, then there will be mechanisms by which this happens. These mechanisms are the kernel of this activity and a set of 11 are proposed together with a description of their possible effects on individuals, providers and employers. Mechanisms might also be termed ‘drivers’ of LLL and each one may act on different stakeholders in different ways and operate differently in changing social, economic and cultural conditions. Thus the complexity of the field of enquiry is recognised. The paper attempts to refine the conceptualisation of mechanisms that work through the aspirations of individuals, the planning process of providers and the needs of employers. The paper also outlines some tentative ideas for empirical analysis of the interactions that are at the heart of the activity." (author's abstract)
Keywords: G 2.2.4 Lebensbegleitendes & lebenslanges Lernen; OECD-Staaten; Berufsbildungssystem; Lebenslanges Lernen; Bildungsträger